Identification of a novel nuclease activity in human DDX49 helicase - Ashley J. Parkes; Sabesan Anandavijayan; Anna Lou-Hing; Olivia Downs; Tom Killelea; Louise Martin; Fiorela Kapllanaj; Edward L. Bolt (Royal Society Open Science)
Human DDX49 is an emerging target in cancer progression and retroviral diseases through its essential roles in nucleolar RNA processing. Here, we identify nuclease activity of human DDX49, which requires active site aspartate residues within a conserved region of metazoan DDX49s that is absent from yeast and archaeal DDX49 homologues. We provide evidence that DDX49 nuclease activity is facilitated by its helicase activity. Using CRISPR-Cas9 genetic editing, we show that a heterozygous (DDX49+/−) U2OS cell line is defective at cell migration, a phenotype supporting the association of DDX49 with cancer cell invasiveness. Measurement of RNAs in DDX49+/− indicates that DDX49 is required to sustain levels of 5.8S rRNA.